Presentación Editorial - Guadarrama Muñoz, Alma Cossette; Meneses Ruiz, Dulce María; Gómez Ramírez, Eduardo; Salazar, Juan Rodrigo; Flegl, Martin; Vázquez Espinoza de los Monteros, Roberto Antonio (Revista del Centro de Investigación de la Universidad la Salle, 2020)
-